Jenis dan pemangsaan scymnus sebagai predator kutu perisai kelapa aspidiotus destructor di Sleman=The species and Predation o/Scymnus as a Predator of Coconut Scale-Insect Aspidiotus destructor in Sleman - Syauta, E.I.; Mahrub, E; Wagiman, FX ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Apredaceous cocrinelid, Scymnus spp., was explored and collected in the coconut ecosystem in sub districts of Minggir, Moyudan, and Godean, in Sleman District. Transect method was applied to sample 40 trees for each of sub district. Morphological characteristics of the adult Scymnus spp. were identified in the Biological Control Laboratory to distinguish among species. Predation rate of the Scymnus spp. against the coconut scale-insect (Aspidiotus destructor Signoret) was also conducted in the laboratory. The results showed that in the coconut ecosystem, there were seven species of Scymnus namely Scymnus apiciflavus, Scymnus sp. A, Scymnus sp. B, Scymnus sp. C, Scymnus sp. D, Scymnus sp.E, and Scymnus sp. F. They were morphologically different in colour, size and pattern on elytra. The S. apiciflavus was the most dominant (61,25%). The predatien rate of the Scymnus spp. adults without sexing was significantly affected by their body size. The biggest body size of S. apiciflavus (2.1 - 2.3 mm) preyed on the coconut scale-insect (10 individuals/24 hours) was larger significantly than those little ones (1.20 -1.98 mm) that only preyed as many as 5 individuals/24 hours.